Identifying Barriers and Areas of Focus to Improve the Publication Practices among Paediatricians in Nepal - Dhakal, Ajaya Kumar; Neopane, Arun Kumar; Thapa, Moon; Singh, Neeti; Shrestha, Devendra (Journal of Nepal Health Research Council, 2025)
Background: Medical research publications in Nepal have remained relatively uncommon over the last decade. However, recent growing research interest among clinicians in Nepal has emphasised the need to identify and address key barriers to strengthen the research-publication process. This study aimed to identify these barriers and focus areas for improving publication practices among paediatricians in Nepal.Methods: A cross-sectional study was conducted among Nepali paediatricians from 15 January to 15 May 2024 using a semi-structured questionnaire distributed via Google Forms. The survey included Likert-scale, open-ended, and closed-ended questions on research-publication barriers, research practices, motivation, and recommendations for improvement.Results: A total of 293 participants (male: 60.1%) responded to the survey. Of these, 35.2% worked in government hospitals, 38.6% were subspecialists, and 54.9% had additional responsibilities beyond their paediatric work. Furthermore, 77.5% of paediatricians had publications, with 78% and 95.15% as principal authors and co-authors, respectively. Systematic reviews and meta-analyses were deemed to be the most challenging, whereas cross-sectional studies were the easiest to conduct. Academic recognition (73.7%) was the primary motivation for publishing, whereas the most significant barrier was being overwhelmed by clinical work (64.5%). Time management (96.1%) and clinical work responsibilities (93.2%) were the main challenges in the manuscript preparation. Ghost authorship (14%) and gift authorship (32.6%) were the most common issues related to authorship. Most participants (80.5%) believed that training in manuscript writing and research methodology could improve the quality and quantity of the research publications.Conclusions: Paediatricians in Nepal face several publication barriers, which can be addressed through increased funding, improved resources, and enhanced research training.Keywords: Barriers; Nepal; paediatrician; publication; research.